Audit lags in Scottish local authority financial reporting / Asmah Abdul Aziz and David Heald - Abdul Aziz, Asmah; Heald, David (Faculty of Accountancy & Accounting Research Institute (ARI), 2004)
Timeliness has been regularly identified as an essential characteristic of effective financial reporting, in both the public and private sectors. This paper systematically investigates the timeliness of Scottish local authority financial reports over the study period 1989-90 to 1995-96. It considers how audit lags can be measured and provides descriptive statistics, before setting out its empirical methodology. It innovates in terms of using Fixed Effects regressions and of then reformulating the problem in terms of non-compliance with externally imposed ceilings on audit lags, so that Logit regressions can be estimated. The regression results on audit lag provide a reasonably consistent picture, whether using OLS or Fixed Effects methodology. The auditing variables are shown to be important: audit lag increases when there is an audit qualification, when there is a change in auditor, and when the audit is done by the Accounts Commission (a public body), rather than a private auditor.